ECG CHANGES IN ACUTE MYOCARDIAL (AMI) - Kholboboyeva Sh.A. (Central Asian Journal of Medicine, 2025)
Acute myocardial infarction (AMI) is one of the most critical cardiovascular emergencies, primarily caused by sudden occlusion of coronary arteries, leading to ischemia and necrosis of heart muscle tissue. The electrocardiogram (ECG) is the most accessible, rapid, and reliable diagnostic tool used to detect and monitor AMI. This article reviews the characteristic ECG changes seen in AMI, including ST-segment elevation, ST-segment depression, pathological Q wave formation, and T wave inversion. It distinguishes between ST-elevation myocardial infarction (STEMI) and non-ST-elevation myocardial infarction (NSTEMI), explaining their diagnostic criteria and ECG features.